The Frame Analysis of Social Movements: The Illustration of A Dynamic Approach to Framing - Zhigadlo, Konstantin V. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Politologiâ (Online), 2023)
There is a diversity of approaches to the use of frame analysis in political studies of social movements. In this study, the concept of framing is considered as an analytical tool for considering the processes associated with civic activism of social movements’ representatives and their subjective coverage of these processes within the framework of positioning themselves in social media. The study presents the so-called “dynamic approach” to framing as the most adequate to the subject of research. It is presented in application to the case of the modern Russian political movement “Future. Society” and the campaigns of its activists to protect the Bitsevsky forest from development in 2022-2023. This example describes various opportunities provided to researchers by frame-analytical optics for working with the analysis of social movements. In particular, it can deepen the understanding of the reasons for the emergence of new social movements in modern Russian public space, their gaining popularity and support among the Internet audience and the mobilization of their activists. In addition, the study suggests that researchers consider a number of new questions about the essence of frames and their connection with narratives and storytelling.